THE EFFECT OF THE DOE WEIGHT ON HER REPRODUCTIVE EFFICIENY - Ahmed, Mohammad Ebrahim; Hussain, Hussain Yawr (The Iraqi Journal of Veterinary Medicine, 2021)
Thirty-six local dose have been used and were divided in to three groups sacording to weight, in each group twelve dose. In the first group the weights of the dose were higher than ( 2.5 kgs) and less than (3 kgs). The second groups was higher than 3 kgs) and less than (3.5 kgs). The third group was higher than (3.5 kgs) and less than (4 kgs). The aim of this study was to obtain the effect of doe weight on her reproductive efficiency (gestation period, litter size, litter weight at birth and weaning, growth rate of offspring preweaning, conception rate and preweaning mortility). The weight of the doe had no significant effect upon the gestation period and this period was 30.9, 31.2, 31.3 days for the three groups respectively, on the other hand the litter size was affected significantly by doe weight and litter size was at birth and preaweaning (5.1 , 5.8 and 6.2), (4.5, 5.3 and 5.7) for the three groups respectively. The offspring weight at birth and weaning was affected significantly by doe weight and this weight was (40.1 , 48.2 and 53.3 gms), (203.6, 227.5 and 233.8 gms) for the three groups respectively while the conception rate was not affected by doe weight. The mortility percentage in the prewaning period was not significantly by doe weight